xxx - Taubah, Mufatihatut (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2012)
The Koran tells us of a father who has a high sense of affection towards his son, so it always came out the advices of full power of wisdom. He is Luqmân, historical figures of the past, a very wise leader who became a symbol of wisdom. He was not a prophet or a messanger, but his name immortalized by God to be the name of one of Koranic surah and has 34 verses. From this background, I try to explore what and how the strategies and steps undertaken by Luqmân al-Hakîm in educating his son to the quality of the highest wisdom. Searching around this topic lead me to the conclusion; First, tawhîd (Oneness of Allah) means to not associate with any of God and God is almighty Essence knows everything without any limit. Second, worship (‘ibâdah), is an effort to get closer to him by way of carrying out the order and away from the ban. Thirdly, akhlâq al-karîmah (noble). The message here is the morality of the ban to be arrogant and look down on others, walking with a simple and polite and gentle in speech. Fourth, teaching methods undertaken by Luqmân is maw‘izah (advising), which provides advice as the basic affection without any threat or intimidation. Fifth, before delivering maw‘izah, Luqmân took his son to think critically and look at existing social reality, so that the child was acutely aware of good and bad effect of a deed",